How to be a pirate - Cowell, Cressida (New York : Little, Brown, 2004)
other books in series Chronicles the adventures and misadventures of Hiccup Horrendous Haddock the Third as he embarks on a quest to pass the training to becomea full-fledged member of his Viking clan, the Tribe of the Hairy Hooligans.
How to train your dragon -- How to be a pirate -- How to speak dragonese -- A hero's guide to deadly dragons -- How to be a pirate -- How to twist a dragons' tale.
Title from container.
6.7
3-6
Keywords: Haddock, Hiccup Horrendous, III (Fictitious character) -- Juvenile fiction; Vikings -- Juvenile fiction; Dragons -- Juvenile fiction; Haddock, Hiccup Horrendous, III (Fictitious character) -- Fiction; Vikings -- Fiction; Dragons -- Fiction; Humorous stories; Haddock, Hiccup Horrendous, III (Fictional character) -- Fiction; Vikings -- Fiction; Dragons -- Fiction; Humorous fiction; Humorous fiction